Introducing Micronaut : build, test, and deploy JAVA microservices on Oracle Cloud - Sharp, Todd Raymond (Apress, 2022)
The microservice architecture has been adopted by many developer teams around the world. To be successful, it's crucial that you understand how to program a microservice and get it running in the cloud. This book will walk you through the process of how to build, test, and deploy a Java-based Micronaut microservice to the Oracle Cloud with GitHub Actions. You'll learn how to create a Virtual Machine (with both the Oracle Cloud Infrastructure (OCI) CLI and the OCI Gradle Plugin), as well as create and deploy the microservice as a Docker container that can be stored in Oracle Container Infrastructure Registry (OCIR) and deployed to an Oracle Kubernetes Engine (OKE) cluster. The microservice will use Micronaut Data for persistence, Testcontainers for testing, and Liquibase to manage your Oracle DB production schema. After reading or using this book, you'll be able to build, test and deploy your first microservices using the Micronaut framework, Oracle Cloud and more. What You'll Learn Build and deploy Java-based microservices using Micronaut and Oracle Cloud Run tests and publishing reports Deploy to Oracle Cloud using OCI CLI and the OCI Gradle plug-in Add a persistence tier to the microservice Distribute a microservice with persistence Who This Book Is For Programmers and software developers with experience in Java and microservices programming who are new to Micronaut.